DECISION SUPPORT SYSTEM PENYALURAN KREDIT USAHA RAKYAT (KUR) MIKRO MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Aisyah, Nurul; Merlina, Nita (Jurnal Pilar Nusa Mandiri, 2013)
During the period of 2008, the distribution of KUR (Kredit Usaha Rakyat) is very effective when compared with the period of 2009. KUR velocity distribution may be due to the high banks in channeling the spirit of KUR, is quite effective dissemination among the banking and society, policy ATMR (Aktiva Tertimbang Menurut Risiko) are laxer and the many demands of prospective borrowers KUR decent but less bankable. The purpose of this paper is making obtaining priority weight of each factor and alternative options to choose borrowers who received micro-enterprise credit people with the greatest priority. The method this study outlined three stages in solving the problem. The first phase, the analysis was conducted to analyze the problem. The second step is data collection began with the distribution of questionnaires, observation, interview, and literature study. Data analysis phase as the third stage, data analysis methods will be used is Analytical Hierarchy Process (AHP) in decision-making with the Expert Choice program analysis which is computer software to determine the choices in making decisions with multiple criteria decision making based on the methodology developed by Saaty. Results Decision Support system Kredit Usaha Rakyat Mikro disbursement by the banks which consists of six criteria: income level, a frequency of credit, length of business, venture capital, education, loan repayment. The highest weighting is the criteria for venture capital, followed by the frequency of credit, length of business, income level, educational level, and the last time loan repayment. Priority for the alternative name for the micro business sector borrowers candidate Peoples Business Loan (KUR) Micro getting KUR Micro is Food Enterprises, grocery and Business Enterprises Business Services, and Agriculture and Fisheries.